Characteristics of the circumstances of formation, clinical and morphological manifestations, course and assessment of the degree of gravity of damage in cases of facial injuries in children and adolescents - Mishalov, V.; Kozlov, S.; Gurina, O.; Garazdiuk, M.; Plevinskis, P.; Zubko, M. D.; Мішалов, В. Д.; Козлов, С. В.; Гуріна, О. О.; Гараздюк, М.С.; Плевінскіс, П. В.; Зубко, Марія Дмитрівна (My University, 2025)
Objective. To investigate the circumstances, clinical and morphological patterns, progression, and severity assessment of facial injuries in children and adolescents, with attention to age and gender differences. Materials and Methods. The research encompassed 203 Expert Conclusions from the archives of the Kyiv Regional and Kyiv City Clinical Bureau of Forensic Medical Examination, 177 Expert Conclusions from the Dnipro Regional Bureau of Forensic Medical Examination, and 123 inpatient records from the Department of Maxillofacial Surgery at Kyiv Children’s Hospital No. 7. These data pertained to forensic investigations of facial trauma cases in pediatric populations. The study design incorporated a detailed analysis based on both gender and age groups to explore relevant patterns. Results The findings revealed that males were more frequently affected by facial injuries, comprising 350 cases (69.6%) out of 503 analyzed, compared to 153 cases (30.4%) involving females. Among all pediatric cases, younger school-aged children (3‑6 years) accounted for 132 cases (26%), while older school-aged children (12‑18 years) comprised the largest subgroup with 197 cases (40%). Morphological analysis showed that in children under 3 years, injuries were primarily confined to the soft tissues of the face and oral cavity. Conversely, children aged 7‑11 years and adolescents were more prone to maxillofacial traumas, including fractures of the facial skull bones, often accompanied by mild to severe traumatic brain injuries. Statistical analysis demonstrated no significant differences in the average healing times among contused, bite-related, and lacerated facial wounds across different pediatric age groups (p > 0.05). Мета роботи – проаналізувати обставини утворення, клінічні та морфологічні прояви, перебіг та оцінку ступеня тяжкості ушкоджень обличчя у дітей та підлітків, враховуючи їх вік та стать. Матеріали та методи. Матеріалом дослідження були 203 «Висновки експерта» з архіву Київського обласного і Київського міського клінічного бюро судово-медичної експертизи, 177 «Висновків експерта» з архіву Дніпровського обласного бюро судово-медичної експертизи, які стосувались судово-медичних експертиз (досліджень) у випадках травм обличчя дітей та підлітків; 123 карт стаціонарного хворого відділення щелепно-лицевої хірургії Київської дитячої лікарні № 7. Дизайн дослідження побудований з урахуванням статі та віку.
Характеристика обставин утворення, клінічних і морфологічних проявів, перебігу та оцінки ступеня тяжкості ушкоджень у випадках травм обличчя у дітей та підлітків
Keywords: Forensic Medical Examination; Children; Facial Trauma; Bodily Injuries; Degree of Gravity; судово-медична експертиза; діти; травма обличчя; тілесні ушкодження; ступінь тяжкості